A Study of Learners’ Writing Anxiety in EFL Context - Ari Prasetyaningrum; Adib Nazri; Maman Asrobi (Universitas Pendidikan Mandalika, 2021)
The present research purposes were to find the factors of students’ writing anxiety and to know what the type of writing anxiety in writing encountered by the participants who followed writing for academic communication course of English education study program at Hamzanwadi University, Nusa Tenggara Barat, Indonesia. This study was categorized as descriptive quantitative method research. The researcher took 15 subjects who were chosen by using purposive sampling. The data collection methods were two closed-ended questionnaires, then second language writing anxiety inventor (SLWAI) designed by Cheng and Causes of Writing Anxiety Inventory (CWAI) proposed by Reraei and Jafari were applied to obtain the data. Observation and interviews were conducted to strengthen the result. The finding of research proved that the highest writing anxiety was avoidance behavior, which turned out the most predominant type among other types of writing anxiety which could be known from the highest mean score. Then there are four main causes that trigger writing anxiety. They were high frequency of writing assignments (25,3 %), low self-confidence in writing (16,87%), and time pressure. (10,79%), and problems with topic choice (10,79 %).